Physiological differences between female limited, alternative life history strategies: The Alba phenotype in the butterfly Colias croceus. (May 2018) - Woronik, Alyssa; Stefanescu, Constanti; Käkelä, Reijo; Wheat, Christopher W.; Lehmann, Philipp
Abstract: Across a wide range of taxa, individuals within populations exhibit alternative life history strategies (ALHS) where their phenotypes dramatically differ due to divergent investments in growth, reproduction and survivorship, with the resulting trade-offs directly impacting Darwinian fitness. Though the maintenance of ALHS within populations is fairly well understood, little is known regarding the physiological mechanisms that underlie ALHS and how environmental conditions can affect the evolution and expression of these phenotypes. One such ALHS, known as Alba, exists within females of many species in the butterfly genus Colias . Previous works in New World species not only found that female morphs differ in their wing color due to a reallocation of resources away from the synthesis of wing pigments to other areas of development, but also that temperature played an important role in these trade-offs. Here we build on previous work conducted in New World species by measuring life history traits and conducting lipidomics on individuals reared at hot and cold temperatures in the Old World species Colias croceus . Results suggest that the fitness of Alba and orange morphs likely varies with rearing temperature, where Alba females have higher fitness in cold conditions and orange in warm. Additionally shared traits between Old and New World species suggest the Alba mechanism is likely conserved across the genus. Finally, in the cold treatment we observe an intermediate yellow morph that may have decreased fitness due to slower larval development. This cost may manifest as disruptive selection in the field, thereby favoring the maintenance of the two discrete morphs. Taken together these results add insights into the evolution of, and the selection on, the Alba ALHS.